2004
DOI: 10.1128/iai.72.6.3204-3217.2004
|View full text |Cite
|
Sign up to set email alerts
|

Virulent and Avirulent Strains ofFrancisella tularensisPrevent Acidification and Maturation of Their Phagosomes and Escape into the Cytoplasm in Human Macrophages

Abstract: Francisella tularensis, the agent of tularemia, is an intracellular pathogen, but little is known about the compartment in which it resides in human macrophages. We have examined the interaction of a recent virulent clinical isolate of F. tularensis subsp. tularensis and the live vaccine strain with human macrophages by immunoelectron and confocal immunofluorescence microscopy. We assessed the maturation of the F. tularensis phagosome by examining its acquisition of the lysosome-associated membrane glycoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
440
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(468 citation statements)
references
References 52 publications
(46 reference statements)
25
440
0
1
Order By: Relevance
“…Each of these portals of entry is a unique immunological niche so F. tularensis needs multiple ways to evade and/or modulate the immunological response. To date, the best-characterized F. tularensis immune evasion is its ability to invade host macrophages and escape the phagolysosomal degradation pathway (53)(54)(55). In this study, we identified a mechanism used by F. tularensis to alter both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these portals of entry is a unique immunological niche so F. tularensis needs multiple ways to evade and/or modulate the immunological response. To date, the best-characterized F. tularensis immune evasion is its ability to invade host macrophages and escape the phagolysosomal degradation pathway (53)(54)(55). In this study, we identified a mechanism used by F. tularensis to alter both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…SCHU S4 lacks coding potential for several expected features. The ability to import complexed ferric (Fe 3+ ) iron should be important for Francisella, because it can escape from the phagosome 22,35 , thereby losing its access to soluble iron present in the acidic milieu. But no previously known ferric iron uptake systems were found in the genome sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, undiscovered mechanisms of virulence are probably encoded in the 33.9-kb pathogenicity island in F. tularensis. Within the macrophage, the bacterium can degrade the phagosomal membrane and escape into the cytosol 22 . We identified genes encoding a phospholipase C acpA (FTT0221) and a phospholipase D family protein (FTT0490), which may have a role in this process.…”
Section: Candidate Mechanisms Of Virulencementioning
confidence: 99%
“…8 Its ability to cause disease is tightly linked to its ability to rapidly escape from the phagosome into the host cytosol where it can replicate to very high numbers. 9,10 Deletion of a genetic locus, the Francisella Pathogenicity Island (FPI), abolishes the ability of F. tularensis to escape into the host cytosol. 11,12 The DFPI mutant remains in a vacuolar compartment, is unable to replicate intracellularly and is highly attenuated in vivo.…”
mentioning
confidence: 99%